The Meaning of Concepts of Human Nature in Organizational Life in Business Ethics Context - Horodecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2014)
The main goal of this paper is to exhibit the role of the concept of human naturefor the ethical orientation of organizational life. Therefore, after presenting somedefinitions of the concepts of human nature, which depict the complexity of thesephenomena, some models of the concepts of human nature are described. Furthermore,the setting of the concepts of human nature in the organizational life isdiscussed. Those concepts can be perceived as a deep-structure of the organizationallife, having an impact not only on the individual behaviour of employeesand managers (like sensibility for human emotions, pro-social engagement, communicationstyle), but also affecting their moral competence and influencingwhole organizational culture – image of the organization, preferred managementstrategies and the way of perceiving justice. Those elements play crucial role inethical attitude of the organization because all those variables support the efficacyof ethical rules and most of them are part of ethical code and corporate ethicalcode. Therefore, it is necessary for an organization to consider implicit and explicitconcepts of human nature on which the organizational culture is based and supportthose concepts, which enables the ethical conduct of the organization andbeing alert especially to the consequences of materialistic/egoistic and competitiveconcepts of human nature. The theses discussed in the paper are supported bysome empirical research studies conducted in this field.